COVID-19: Lessons for the climate change emergency - Manzanedo, Rubén D. (Sci Total Environ, 2020)
The ongoing COVID-19 outbreak pandemic is now a global crisis. It has caused 9+ million confirmed cases and 400,000+ deaths at the time of writing and triggered unprecedented preventative measures that have confined a substantial portion of the global population and established ‘social distancing’ as a new global behavioral norm. The COVID-19 crisis has affected all aspects of everyday life and work, and heavily impacted the global economy. This crisis also offers unprecedented insights into how the global climate crisis may be managed, as there are many parallels between the COVID-19 crisis and what we expect from the imminent global climate emergency. Reflecting upon the challenges of today's crisis may help us better prepare for the future. Here we compile a list, by no means comprehensive, of the similarities and differences between the two crises, and the lessons we can learn from them: (i) High momentum trends, (ii) Irreversible changes, (iii) Social and spatial inequality, (iv) Weakening of international solidarity, and (v) Less costly to prevent than to cure.